Development of Learning Videos Assisted by the Sparkol Video Scribe Application on Science Object Material Class V Elementary School - Perdi; H.M. Lubis, Patricia; Riyanti, Henni (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2024)
This paper presents the development of animated video learning media on object material assisted by the Sparkol Video Cribe application at Class V Elementary School. This research is valid and practical. This research uses the type of research and development (RnD) validated by media experts at 85%, material experts at 84%, and language experts at 82%. Practical stages, in addition, were carried out at the one-to-one stage and in small groups. The population involved five people (one-to-one) with a percentage score of 92.8%. And 15 people (small group) got a percentage score of 84%. Data were obtained through documentation, and questionnaire sheets. Data analysis techniques tested were the validity and practicality of animated video media. The research results show that the animated video media assisted by the Sparkol Video Scribe application has met the valid and practical criteria for use in the learning process.